The Cyber Conundrum. - KROLL, JOSHUA A. (American Prospect)
The article discusses issues concerning the national cyber defense in the U.S. Topics covered include the problem in finding strategies to undermine the very same systems that the U.S. government wants to protect, the principle of the undermine-first and protect-first strategy, the percentage of gross domestic product lost to cybercrime and the right to privacy, and the divide between industry and government in cybersecurity.